Expression Analysis of Retinal G Protein-coupled Receptor and its Correlation with Regulation of the Balance between Proliferation and Aberrant Differentiation in Cutaneous Squamous Cell Carcinoma - Jianglong Feng; Wei Zhang; Wen Zeng; Xian Dong; Yu Wang; Yangguang Gu; Yinghua Lan; Wenxiu Yang; Hongguang Lu (Medical Journals Sweden, 2024)
Retinal G protein-coupled receptor (RGR), a photosensitive protein, functions as a retinal photoisomerase under light conditions in humans. Cutaneous squamous cell carcinoma (cSCC) is linked to chronic ultraviolet exposure, which suggests that the photoreceptor RGR may be associated with tumorigenesis and progression of squamous cell carcinoma (SCC). However, the expression and function of RGR remain uncharacterized in SCC. This study analysed RGR expression in normal skin and in lesions of actinic keratosis, Bowen's disease and invasive SCC of the skin with respect to SCC initiation and development. A total of 237 samples (normal skin (n = 28), actinic keratosis (n = 42), Bowen's (n = 35) and invasive SCC (n = 132) lesions) were examined using immunohistochemistry. Invasive SCC samples had higher expression of RGR protein than the other samples. A high immunohistochemical score for RGR was associated with increased tumour size, tumour depth, Clark level, factor classification, and degree of differentiation and a more aggressive histological subtype. In addition, RGR expression was inversely correlated with involucrin expression and positively correlated with proliferating cell nuclear antigen (PCNA) and Ki67 expression. Furthermore, RGR regulates SCC cell differentiation through the PI3K-Akt signalling pathway, as determined using molecular biology approaches in vitro, suggesting that high expression of RGR is associated with aberrant proliferation and differentiation in SCC.